المسار النموذجي لتدقيق اداء الدور الاشرافي للبنك المركزي العراقي على المصارف الخاصة على وفق معايير الاجهزة العليا للرقابة المالية والمحاسبة: بحث تطبيقي في ديوان الرقابة المالية الاتحادي (Journal of Accounting and Financial Studies ( JAFS ), 2020)
With today's rapid and full of dangers the world banking sector is one of the most vital sectors at risk, and on the supervisory bodies responsible for monitoring the work of banks to take an active role in influencing the banks and put on the right track and is compatible with internationally approved curriculum. The lie of the research problem in the weak supervisory role of the Central Bank for banks in general and private banks in particular, limited the process of performance audit carried out by the Federal Office of Financial Supervision in auditing oversight role of the Central Bank control over the banks, according to the methods of performance audit followed by the upper bodies of financial control and accounting, And it was based on research in solving its problems first Frditbn underperformance supervisory   of the Central Bank in monitoring the banking system, according to the standards of supervisory control followed internationally weaken the banking system and displays it to the risk of threatening the continuation and reduce the level of its contribution to the achievement of the target of the country's economic development. The second and contributes to audit the performance of supervisory role of the Central Bank in its role towards developing supervisory and regulatory mechanisms and to ensure the upgrading of the methods of control over the banks in order to ensure the advancement of the banking sector and support .The research has come to a set of conclusions , including the coordination and supervision of the Supreme Audit Institutions and supervisory control of central banks to banks and private banks, especially important factors for the development of economy in the country, the key role that banks play in building a strong economy.